2015
DOI: 10.1007/s00464-015-4456-7
|View full text |Cite
|
Sign up to set email alerts
|

Has endoscopic (TEP, TAPP) or open inguinal hernia repair a higher risk of bleeding in patients with coagulopathy or antithrombotic therapy? Data from the Herniamed Registry

Abstract: Introduction Inguinal hernia operations in the presence of antithrombotic therapy, based on antiplatelet or anticoagulant drugs, or existing coagulopathy are associated with a markedly higher risk for onset of postoperative secondary bleeding. To date, there is a paucity of concrete data on this important clinical aspect of inguinal hernia surgery. Up till now, the endoscopic (TEP, TAPP) techniques have been considered to be more risky because of the extensive dissection involved.Patients and methodsOut of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
7

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 12 publications
1
20
0
7
Order By: Relevance
“…A previous report showed that patients receiving antithrombotic therapy or with existing coagulopathy who had undergone inguinal hernia operation have a fourfold higher risk (3.9%) for postoperative secondary bleeding . In the present study, preperitoneal dissection was performed gradually from the space under the intraumbilical skin incision with standard laparoscopic instruments, such as laparoscopic coagulation shears and blunt dissectors, because blind balloon dilation of the preperitoneal space could have caused intraoperative bleeding and a poor operative field.…”
Section: Discussionmentioning
confidence: 85%
“…A previous report showed that patients receiving antithrombotic therapy or with existing coagulopathy who had undergone inguinal hernia operation have a fourfold higher risk (3.9%) for postoperative secondary bleeding . In the present study, preperitoneal dissection was performed gradually from the space under the intraumbilical skin incision with standard laparoscopic instruments, such as laparoscopic coagulation shears and blunt dissectors, because blind balloon dilation of the preperitoneal space could have caused intraoperative bleeding and a poor operative field.…”
Section: Discussionmentioning
confidence: 85%
“…Regarding inguinal hernia surgery alone, postoperative bleeding is the most frequent adverse event [16, 17]. A recent registry-based analysis of 82,911 patients undergoing open or endoscopic [transabdominal preperitoneal patch plasty (TAPP), total extraperitoneal patch plasty (TEP)] inguinal hernia repair showed a fourfold higher risk for onset of postoperative bleeding in patients with existing anticoagulation or antithrombotic therapy [10]. Surprisingly, the endoscopic procedures (TAPP, TEP) showed lower postoperative bleeding rates compared to open inguinal hernia repair, although the endoscopic techniques were deemed as being more likely to cause postoperative bleeding due to their more extensive tissue dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the endoscopic procedures (TAPP, TEP) showed lower postoperative bleeding rates compared to open inguinal hernia repair, although the endoscopic techniques were deemed as being more likely to cause postoperative bleeding due to their more extensive tissue dissection. Additionally, larger hernia defect size, male gender, higher ASA score, and recurrent operation were identified as significant risk factors for postoperative bleeding in the registry population [10]. However, data on the risk of postoperative bleeding among patients undergoing incisional hernia repair are rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. Thrombozytenaggregationshemmern nicht möglich, kann bei sorgfältiger Präparation und Blutstillung dennoch laparoendoskopisch operiert werden. Registerdaten zeigen, dass das laparoendoskopische Operieren im Vergleich zum offenen kein erhöhtes Risiko für Nachblutungen darstellt [5].…”
Section: Präoperative Vorbereitungunclassified